2008
DOI: 10.1073/pnas.0801919105
|View full text |Cite
|
Sign up to set email alerts
|

Extinction and the spatial dynamics of biodiversity

Abstract: The fossil record amply shows that the spatial fabric of extinction has profoundly shaped the biosphere; this spatial dimension provides a powerful context for integration of paleontological and neontological approaches. Mass extinctions evidently alter extinction selectivity, with many factors losing effectiveness except for a positive relation between survivorship and geographic range at the clade level (confirmed in reanalyses of end-Cretaceous extinction data). This relation probably also holds during ''no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
165
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(171 citation statements)
references
References 92 publications
(61 reference statements)
4
165
2
Order By: Relevance
“…Our view of the dinosaur radiation is in line with Jablonski's (1986Jablonski's ( , 1991Jablonski's ( , 2001Jablonski's ( , 2005Jablonski's ( , 2008) view of macroevolution: that "successful" organisms must navigate both background and mass extinction events in order to survive and prosper. The dinosaurs were clearly successful during the first 30+ million years of their history in the Middle and Late Triassic.…”
Section: The Evolutionary Radiation Of Dinosaurs: Current Statusmentioning
confidence: 52%
“…Our view of the dinosaur radiation is in line with Jablonski's (1986Jablonski's ( , 1991Jablonski's ( , 2001Jablonski's ( , 2005Jablonski's ( , 2008) view of macroevolution: that "successful" organisms must navigate both background and mass extinction events in order to survive and prosper. The dinosaurs were clearly successful during the first 30+ million years of their history in the Middle and Late Triassic.…”
Section: The Evolutionary Radiation Of Dinosaurs: Current Statusmentioning
confidence: 52%
“…A negative dependence of extinction on taxon age, previously reported in marine, mainly benthic, genera (5), is here shown to also apply to marine zooplanktic species. This finding points to the importance of abiotic factors in driving extinction; old species and genera tend to be more widely distributed and represented by more local populations, rendering them less susceptible to environmentally driven extinction (38)(39)(40), although Finnegan et al (5) found that additional, unexplained, factors were involved for their data. Note that survivorship trajectories for short-lived taxa (taxon durations <0.2 My) are identical in the pK-Ordovician and K-Silurian (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…For instance, in contrast to calcareous nannoplankton, another group of calcifying plankton, the calcareous dinoflagellates, experienced no major extinction at the K/Pg (11). All calcareous rudist bivalve species were lost, but ∼40% of other bivalve genera survived (46). In contrast to planktics, benthic foraminifera with calcareous shells survived the event relatively intact, whether inhabiting shallow or deep waters (47).…”
Section: Discussionmentioning
confidence: 99%